Childhood homelessness, resilience, and adolescent mental health: A prospective, person‐centered approach. Issue 12 (19th December 2019) - Herbers, Janette E.; Cutuli, J. J.; Keane, Joanna N.; Leonard, Jake A.
Abstract: School districts and other service providers are increasingly aware of the substantial mental health needs of students experiencing family homelessness. Past findings are mixed regarding whether homelessness conveys unique risk beyond the risks associated with extreme poverty. With prospective longitudinal data on homelessness experiences across childhood, we utilized latent profile analysis as a person‐centered approach to conceptualizing mental health outcomes in adolescence for 3, 778 youth. We considered literal family homelessness as well as families living doubled‐up, and we employed propensity score matching to identify a comparison group of nonhomeless students balanced across a range of covariates to address systematic bias. Results indicated that students who experienced literal homelessness during childhood were significantly less likely to demonstrate profiles of resilience in mental health functioning. We considered our approach and findings in light of challenges and opportunities particularly relevant to the school context.